The Urban Phenomenon in Belén Gopegui's Deseo de ser punk; or, Martina's Acoustic Assault. Issue 4 (21st April 2021) - Martínez, Michael L.
Abstract: This article adopts an urban cultural studies method in order to examine the representation of Henri Lefebvre's urban phenomenon in Belén Gopegui's Deseo de ser punk (2009). The narrative is focalized through the adolescent perspective of the protagonist/narrator Martina, a resident of Madrid, Spain, and portrays the development of the conflicting material bases of urbanized consciousness formation. Gopegui, moreover, explores how the alienation that attaches to urbanized consciousness can potentially give rise to counterhegemonic urban practices that oppose capital's conceived city, leading climactically to Martina's public demand for a renewed, lived city, what the alienated youth calls an acoustic assault.